Yearbook on the African Union. Volume 2 (2021) - Engel, Ulf (2023)
This is the second edition of the Yearbook on the African Union. The YBAU is first and foremost an academic project that provides an in-depth evaluation and analysis of the institution, its processes, and its engagements. Despite the increased agency in recent years of the African Union in general, and the AU Commission in particular, little is known - outside expert policy or niche academic circles - about the Union's activities. This is the gap the Yearbook on the African Union wants to systematically address. It seeks to be a reference point for in-depth research, evidence-based policy-making and decision-making.
Introduction / Ulf Engel -- The Annual Interview : Implementation of the African Union's Twin Financial and Institutional Reforms / Alexandre T. Ratebaye -- The State of the Union / Ulf Engel -- The Democratic Republic of Congo's Chairmanship of the African Union / Hans Hoebeke and Onesphore Sematumba -- Education, Science and Technology / Ulf Engel -- Governance / Annie Barbara Hazviyemurwi Chikwanha -- Health / Edefe Ojomo and Habibu Yaya Bappah -- Infrastructure / Tim Zajontz -- Peace and Security / Dawit Yohannes Wondemagegnehu -- Regional Integration and Trade / Bruce Byiers -- Strategic Partnerships / Ulf Engel -- Women and Youth / Awino Okech.
Includes bibliographical references and index.
English.
Keywords: African Union; African Union; International relations; Relations internationales; international relations; International relations; Politics and government; Social conditions; Africa -- Politics and government; Africa -- Social conditions; Afrique -- Politique et gouvernement; Afrique -- Conditions sociales